The body, the city, the global: spaces of catastrophe in Ian McEwan's Saturday. Issue 4 (7th June 2017) - Colombino, Laura
ABSTRACT: The paper analyses Ian McEwan's Saturday, interrogating its representation of the body as a metaphor of outer spaces, urban and global. In a post-9/11 context, Saturday engages with catastrophic imaginaries and social anxieties by illuminating the entanglement of the spaces of terror with the bodily and more specifically the neurological dimension. If genetics and neuroscience have spatialised our bodies in novel ways, this article shows how in Saturday the architecture of the brain is made to relate to the larger networks of the city and how the city, in its turn, becomes the lens through which international scenarios can be visualised. This interconnectedness is reinforced by the theme of catastrophe whose key is struck at three different pitches: the genetic risk endangering the individual; the urban risk jeopardising the family; the global risk threatening civilisation. The illegibility of the post-traumatic space is resolved symbolically through the conduit of the somatic self. Corporeality frames the whole novel: the incipit echoes the innatist portrayal of body and mind predicated by neuroscience; the end suggests our biological predisposition to human empathy and implies that only a narrative of human interconnectedness (both scientific and artistic) can reconcile us with the world and ourselves.